Stable and inert manganese complexes for magnetic resonance imaging - Ndiaye, Daouda; Tóth, Éva (Comptes Rendus. Chimie)
Paramagnetic Mn$^{2+}$ complexes are intensively investigated as alternatives to replace the currently used, Gd-based clinical contrast agents in Magnetic Resonance Imaging (MRI). Manganese is an essential metal which alleviates its potential toxicity and the environmental concerns related to the use of Gd$^{3+}$. Thanks to its five unpaired electrons and slow electron spin relaxation, Mn$^{2+}$ is a very efficient relaxation agent. Given the high doses required for in vivo MRI, Mn$^{2+}$ needs to be chelated in thermodynamically stable and kinetically inert complexes, despite its natural presence in the body. We survey here the latest developments in the chemistry and the preliminary in vivo MRI evaluation of Mn$^{2+}$ complexes. We specifically focus on the molecular ligand design, including linear, macrocyclic and bicyclic (bispidine) chelators that allowed for substantially enhanced kinetic inertness of the complexes, as well as for ligand selectivity for Mn$^{2+}$ versus the main biological competitor Zn$^{2+}$. In addition to the $+2$ form of manganese, Mn$^{3+}$ is also paramagnetic in the high-spin state, with promising relaxation properties among porphyrin complexes. Finally, examples will be presented to demonstrate the first steps towards the development of redox sensors based on the Mn$^{2+}$/Mn$^{3+}$ switch, detectable in $^{1}$H or in $^{19}$F MRI.